THE EFFECT OF SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) ON ANXIETY DURING THE ACTIVE PHASE I LABOR - Lestari Puji Astuti; Ikha Siswiyanti; Sonhaji Sonhaji (Poltekkes Kemenkes Semarang, 2022)
Anxiety often occurs in maternity mothers and not being treated will have an impact on the mother's physical and psychological. As many as 9% of mothers who experience anxiety will increase pain and result in a long labor process. Therefore, it is necessary to take action by the midwife to control anxiety so that the delivery process runs smoothly. SEFT is a psycho-religious therapy that can reduce maternal anxiety without causing side effects. To determine the effect of SEFT on anxiety in maternity mothers during the active phase I. This is pre-experimental research with one group pre-post-test design. This study used purposive sampling. The statistical test used the dependent t-test. The average anxiety score before SEFT therapy was 24.44, with a minimum score was 20 and a maximum score was 29. The average anxiety score after SEFT therapy was 19.06, with a minimum score was 14 and a maximum score was 25. The results of the dependent t-test showed a p-value 0.000 (0.05) which means that there is a difference in the average anxiety score before and after the application of SEFT. There is an effect of the Spiritual Emotional Freedom Technique (SEFT) on reducing maternal anxiety scores during the Active Phase I in the Dempet Health Center Work Area. The application of SEFT can increase the relaxation that can be obtained from conditions of solemnity, sincerity, resignation, confidence, and gratitude so that mothers can produce responses that can reduce anxiety during the delivery process.